La afectividad de los docentes del nivel Inicial en la Enseñanza - Aprendizaje - Núñez Montenegro, Yovany Ceci (2007)
In the beginning of the history of human civilizations do not seem to have been a speech on the separation between the cognitive and affective, affection being one of the primary processes basically as secondary cognitive process. Most recently in contemporary times. separation of affective and cognitive processes where it appears that man is categorized by: learning is cognitive and affective desire is. Today it requires the individual to be formed in an integrated way without leaving unnoticed affectivity. Factors favoring affective development, also produce the same result of cognitive development and also the emotional development depends on adequate combination that the individual can do, new learning tasks assigned to him and cognitive development as allow the teachers often provide too much structure in didactic activities. As for the emotional relationship teachers are solely responsible for creating a pleasant environment for children, play, recreation to achieve development responsibility for the boy and girl as well as the attitude of assimilation of knowledge because the child and girl learns more by affection than by intellectual self-concern. The value of expressing affection I defects generated by students in teachers is the beginning of recognizing the classroom; a different dimension usual, ie horn a neutral space where knowledge and intellect relates only; but a space where affective relationships are also interwoven, linkages, partnerships, etc. The effectiveness comes from within the self, to stimuli that provide teachers in the process of learning of children in the preschool stage, as the infant needs, both physiological and psychological unconditional love, both parents and teachers. Chaves says that affectivity is a set of knowledge expressed through actions among people in any social context in which individuals are involved; teachers and students are called to make the classroom a space for building human relations, recognizing the emotions as essential for individual, interpersonal and social development emotion. The effectiveness is based on psychological theories of White and Watts, Simpson and Gray, Rosenshine, Landsheeren and Ausubel Since then studies conducted with affectivity improvement in the learning of preschool teachers t1acia. In affectivity also it influences society often either a pleasant or unpleasant way that will allow the child assessed as it is